Kcnab1 Is Expressed in Subplate Neurons With Unilateral Long-Range Inter-Areal Projections - Tiong, Sheena Yin Xin; Oka, Yuichiro; Sasaki, Tatsuya; Taniguchi, Manabu; Doi, Miyuki; Akiyama, Hisanori; Sato, Makoto (Frontiers Media, 2019)
Subplate (SP) neurons are among the earliest-born neurons in the cerebral cortex and heterogeneous in terms of gene expression. SP neurons consist mainly of projection neurons, which begin to extend their axons to specific target areas very early during development. However, the relationships between axon projection and gene expression patterns of the SP neurons, and their remnant layer 6b (L6b) neurons, are largely unknown. In this study, we analyzed the corticocortical projections of L6b/SP neurons in the mouse cortex and searched for a marker gene expressed in L6b/SP neurons that have ipsilateral inter-areal projections. Retrograde tracing experiments demonstrated that L6b/SP neurons in the primary somatosensory cortex (S1) projected to the primary motor cortex (M1) within the same cortical hemisphere at postnatal day (PD) 2 but did not show any callosal projection. This unilateral projection pattern persisted into adulthood. Our microarray analysis identified the gene encoding a β subunit of voltage-gated potassium channel (Kcnab1) as being expressed in L6b/SP. Double labeling with retrograde tracing and in situ hybridization demonstrated that Kcnab1 was expressed in the unilaterally-projecting neurons in L6b/SP. Embryonic expression was specifically detected in the SP as early as embryonic day (E) 14.5, shortly after the emergence of SP. Double immunostaining experiments revealed different degrees of co-expression of the protein product Kvβ1 with L6b/SP markers Ctgf (88%), Cplx3 (79%), and Nurr1 (58%), suggesting molecular subdivision of unilaterally-projecting L6b/SP neurons. In addition to expression in L6b/SP, scattered expression of Kcnab1 was observed during postnatal stages without layer specificity. Among splicing variants with three alternative first exons, the variant 1.1 explained all the cortical expression mentioned in this study. Together, our data suggest that L6b/SP neurons have corticocortical projections and Kcnab1 expression defines a subpopulation of L6b/SP neurons with a unilateral inter-areal projection. © 2019 Tiong, Oka, Sasaki, Taniguchi, Doi, Akiyama and Sato.